Method of quantitative assessment for diversified software system - Yuan YAO; Chuanxing PAN; Zheng ZHANG; Gaofei ZHANG (Tongxin xuebao)
To instruct the selecting of the redundancy variants for diversified software system at different situations,the evaluation systems of usability,security and performance was constructed by using some diversified software evaluation indicators.Then hierarchical analyzation system (HAS) was introduced based on the three evaluation systems.A real case verify that HAS is practicable at the situation that there are not many variants.